2017
DOI: 10.1098/rsbl.2016.0665
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution of mound-building and grass-feeding in Australian nasute termites

Abstract: Termite mounds built by representatives of the family Termitidae are among the most spectacular constructions in the animal kingdom, reaching 6-8 m in height and housing millions of individuals. Although functional aspects of these structures are well studied, their evolutionary origins remain poorly understood. Australian representatives of the termitid subfamily Nasutitermitinae display a wide variety of nesting habits, making them an ideal group for investigating the evolution of mound building. Because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 7 publications
(8 reference statements)
2
21
0
Order By: Relevance
“…Gross, Borowsky, & Tabin, ; Protas et al., ) as well as in more divergent taxa (e.g. Arab et al., ; Emerson & Koehl, ; Stearns & Fenster, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross, Borowsky, & Tabin, ; Protas et al., ) as well as in more divergent taxa (e.g. Arab et al., ; Emerson & Koehl, ; Stearns & Fenster, ).…”
Section: Introductionmentioning
confidence: 99%
“…In each area, some individuals adapt to a novel niche created by the onset of aridity, and eventually become reproductively isolated from their parent species, which remains in the original niche. Although some studies have found evidence for an association between ancient aridification events and parallel evolution (Arab et al., ; Lo et al., ), the abiotic factors associated with these changes remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Mound‐building has also multiple origins among higher termites, as exemplified by the Australian Nasutitermitinae in which it evolved independently in at least six lineages (Arab et al., 2017). As is the case for shelter tube construction, there is a possibility that all species of Nasutitermitinae share the same behavioral rules and that the species that do not build mounds under natural conditions are able to do so under unusual conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the crown radiation for the spinifex‐specialised phasmid geckos in the mid‐Miocene broadly overlaps with the inferred age of the spinifex radiation (Laver et al, 2017; Skipwith, et al, 2019). Recent work on Australian nasute termites inferred a transition from wood to grass and litter feeding in one major group occurred in the mid‐Miocene, with the switch to exclusive grass feeding in two sister‐pairs (including the spinifex termite Nasutitermes triodea ) inferred to have occurred ~ 5‐6 Mya (Arab, et al, 2017). Alternatively, as vegetation types would have expanded and contracted their distributions with climatic cycles, taxa may have diverged after the emergence of an associated vegetation formation, but during these contraction phases.…”
Section: The Evolution Of Arid Zone Biodiversitymentioning
confidence: 99%